VINOVAL (VISUAL NOVEL MODAL AUXILIARY): A SIMULATOR GAME TO INTRODUCE MODAL AUXILIARY TO STUDENT - Alwinda Fischa Chalysta; Astried Damayanti (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2020)
E-learning is the use of information and computer technologies to create learning experiences. The objective of the research was to develop of VINOVAL. The research design was educational R&D as one research design aimed at developing educational products, like curriculum, syllabus, textbooks, instructional media, etc. Moreover, this research implemented quasi-experimental research design to know the efficacy of the product. The subject of the research was eleventh grade students of SMAN 2 Trenggalek 2019/2020 academic year which consist of 36 experimental group and 36 control group. The research instruments were questionnaires, test, and interview. The questionnaires and test data were analyzed quantitatively, while interview data was analyzed qualitatively. The product was developed in five steps based on students’ needs, recent theories related to the product, developing the educational product, evaluation from the expert who validates the product and field testing the product. The data was calculated by SPSS 25 and the result of sig. 2 tailed in t-test is 0.000 (<0.05), it means there was significant difference between experimental and control groups. From explanation above means that the product of this research, VINOVAL, was an effective learning media to senior high school students to introduce modal auxiliary material. Furthermore, it was suggested for people who find some benefit of this research.